Aksiologi dalam Era Society 5.0: Menyikapi Perubahan Nilai dalam Masyarakat Digital - Intan Alisa Nasution; Khadijah Nur Aini; Edo Adrio; Ahmad Wahyudi Zein (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The Society 5.0 era has brought fundamental transformations in the social structure, technology and value system of society. This research aims to explore the axiological dynamics that occur in the midst of the digital revolution, with the main focus on shifts in fundamental values ​​in the context of digital society. Using the literature review method, this study analyzes various academic sources, scientific journals and related publications to understand the complexity of axiological changes in the digital era. The research approach was carried out systematically by reviewing literature from various scientific disciplines, including sociology, philosophy, anthropology, and information technology. The research results show that digital society is experiencing a significant value transformation, including changes in ethical concepts, aesthetics, social logic and traditional norms. Key findings reveal that digital technology is not just a tool, but an agent of transformation that influences the construction of social values. The digitalization process has encouraged the emergence of a new paradigm in understanding human relationships, identity and social interactions. This research offers a critical perspective on the axiological challenges in integrating traditional values ​​with the dynamics of digital society, and embedding them in the formation of social structures in the Society 5.0 era.